Nadler-based Models of Method Selection in Management Problem-solving - Szarucki, Marek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
Increasing organisational efficiency as a category of management sciences is one of the major challenges for both practitioners and theoreticians of management. Properly selecting methods to solve management problems is one factor that increases organisational efficiency. However, there is a lack of extensive methodological studies addressing method selection in the process of management problem solving. Nadler’s concept of the ideal system may serve as the basis for constructing method selection. The main objective of this study is to present the possibilities of adapting Nadler’s concept in creating the models of method selection in management problem-solving. Deduction and an analysis of the literature were the research methods employed. The article begins by exemplifying Nadler’s concept of an ideal system. This is followed by an original proposal for ideal models of method selection in management problem-solving. Finally, conclusions and suggestions for further research are discussed.